2013
DOI: 10.1007/s10555-013-9464-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen regulates molecular mechanisms of cancer progression and metastasis

Abstract: Oxygen is the basic molecule which supports life and it truly is "god's gift to life." Despite its immense importance, research on "oxygen biology" has never received the light of the day and has been limited to physiological and biochemical studies. It seems that in modern day biology, oxygen research is summarized in one word "hypoxia." Scientists have focused on hypoxia-induced transcriptomics and molecular-cellular alterations exclusively in disease models. Interestingly, the potential of oxygen to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 283 publications
(351 reference statements)
0
8
0
Order By: Relevance
“…Mitochondria together with ROS is known to be associated with cell death [63] and several mechanisms implicate these in necroptosis. Zhang [64] reported a lack of phosphorylation of MLKL during myocardial necroptosis in response to ischemia and oxidative stress.…”
Section: Molecular and Cellular Basics Of Necroptosismentioning
confidence: 99%
“…Mitochondria together with ROS is known to be associated with cell death [63] and several mechanisms implicate these in necroptosis. Zhang [64] reported a lack of phosphorylation of MLKL during myocardial necroptosis in response to ischemia and oxidative stress.…”
Section: Molecular and Cellular Basics Of Necroptosismentioning
confidence: 99%
“…Depending on the specific cells and tissues undergoing stress, HIFα can mediate adaptive responses to hypoxia that include increased erythropoiesis, increased angiogenesis, and reprogramming of metabolism away from oxidative phosphorylation and towards glycolysis and anaerobic fermentation. In addition to its role in response to acute hypoxic stress, the hypoxia response pathway also helps to maintain stem cell niches and tumor growth and metastasis in cancer ( Amelio and Melino, 2015 ; Gupta et al, 2014 ; Ito and Suda, 2014 ). Whereas the major target of oxygen regulation through EGL-9/PHD proteins is HIFα, several studies have shown that EGL-9/PHD oxygen sensors regulate additional proteins as part of the overall hypoxia response ( Lee et al, 2005 ; Koditz et al, 2007 ; Fu et al, 2007 ; Fu and Taubman, 2010 ; Cummins et al, 2006 ; Park et al, 2012 ; Lee et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the plasma membrane disruption, MLKL may also target the mitochondrial membrane and induce mitochondrial disruption by opening the mitochondrial permeability transition pore (mPTP) [121,122]. This can result in an excessive production of reactive oxygen species (ROS), further amplifying cell death [123]. It has recently emerged that these MLKL activities do not immediately cause plasma membrane rupture.…”
Section: Mechanisms Underlying Necroptosis: a Broad Overviewmentioning
confidence: 99%